Pemanfaatan Sistem Informasi Geografi (SIG) Dalam Pemetaan Daerah Rawan Bencana Longsor Di Kecamatan Wih Pesam Kabupaten Bener Meriah - Aprilia, Epa; Novia Zalmita; Fitriani Yulianti; M. Hafizul Furqan (CV. Ulil Albab Corp, 2025)
Wih Pesam Sub-district in Bener Meriah Regency is an area that has a high level of vulnerability to landslides due to geographical conditions dominated by steep slopes, high rainfall, and vulnerable soil types..This research aims to map landslide-prone areas by utilizing Geographic Information System (GIS) technology using the parameters of rainfall, soil type, slope, land cover, and geology. The methods used include overlay, weighting, and scoring techniques based on the guidelines of Puslittanak Bogor (2004). The mapping results show three vulnerability classifications: low (17.8 ha), medium (1,315.7 ha) and high (1,976.6 ha)..The majority of areas are in the high category, indicating a high potential for landslides in the area. The map resulting from this analysis is expected to be a reference in disaster mitigation, development planning, as well as increasing public awareness of landslide risks.